The role of myoglobin degradation in nephrotoxicity after rhabdomyolysis. (25th August 2016) - Zorova, Ljubava D.; Pevzner, Irina B.; Chupyrkina, Anastasia A.; Zorov, Savva D.; Silachev, Denis N.; Plotnikov, Egor Y.; Zorov, Dmitry B.
Abstract: The fate of myoglobin in renal cells was explored in an animal model of rhabdomyolysis known as the pathology highly related to oxidative stress resulting in impairment of renal functioning. The working hypothesis was that the proper degradation of myoglobin in rhabdomyolytic kidney can activate the reparative processes in the tissue. We found that incubation of myoglobin with kidney cells causes its accumulation in the cytoplasm. In rhabdomyolytic rats, the level of heme and free iron in cytoplasm and mitochondria of kidney cells is remarkably increased while inhibition of proteolysis results in further elevation of myoglobin content in the renal tissue. Heme oxygenase and ferritin levels were found to be increased in the kidney tissue at rhabdomyolysis and simulating conditions performed by i/v injection of myoglobin. In addition, the level of peroxidized lipids was high in rhabdomyolytic kidney and became even higher after inhibition of proteolysis by aprotinin. Elevated levels of carbonylated proteins were also observed after rhabdomyolysis, however, if prior to induction of rhabdomyolysis the injection of myoglobin was done, the level of carbonylated proteins dropped versus unprimed kidney tissue thus affording protection to the kidney against oxidative stress. Injection of myoglobin to the rat results in impairment of renal functioning and inhibition of myoglobin degradation in the rhabdomyolytic animal aggravates acute renal failure, demonstrating that degradation of myoglobin is somehow beneficial although it may result in undesired release of free iron which can participate in toxic redox cycling. Highlights: Rhabdomyolysis causes elevated levels of heme and iron in cytoplasm and mitochondria of kidney cells. Inhibition of proteolysis increases levels of myoglobin in kidney cells at rhabdomyolysis. Heme oxygenase and ferritin in rat kidney rise after rhabdomyolysis and its imitation condition. Inhibition of myoglobin and heme degradation impairs renal functioning.